Effects of Military Service and Deployment on Clinical Symptomatology: The Role of Trauma Exposure and Social Support - Moore, Tyler M. (J Psychiatr Res, 2017)
The Marine Resiliency Study-II examined changes in symptomatology across a deployment cycle to Afghanistan. U.S. Servicemembers (N = 1041) received clinical testing at two time points either bracketing a deployment (855) or not (186). Factor analyses were used to generate summary and change scores from Time 1 to Time 2. A between-subject design was used to examine changes across the deployment cycle with deployment (low-trauma, high-trauma, and non-deployed) and social support (low vs. high) as the grouping variables. Insomnia increased post-deployment regardless of deployment trauma (std. effect for high-trauma and low-trauma = 0.39 and 0.26, respectively). Only the high-trauma group showed increased PTSD symptoms and non-perspective-taking (std. effect = 0.40 and 0.30, respectively), while low-trauma showed decreased anxiety symptoms after deployment (std. effect = −0.17). These associations also depend on social support, with std. effects ranging from −0.22 to 0.51. When the groups were compared, the high-trauma deployed group showed significantly worse PTSD and non-perspective-taking than all other groups. Similar to studies in other military divisions, increased clinical symptoms were associated with high deployment stress in active duty Servicemembers, and social support shows promise as a moderator of said association.